HISTORY OF THE DEVELOPMENT OF GAMBELAN BATEL AS AN ACCOMPANIMENT TO LEATHER PUPPET SHOW IN SIBANGGEDE VILLAGE - Surianta, I Nyoman (International Conference on Cultural Studies; Vol 1 (2018): Proceedings International Conference on Cultural Studies, 2018)
Various forms of ensembles (barungan), ricikan (instruments), gamelan owned by Balinese people, are priceless product inheritances which are regional cultural majesty which are very important in the history of Balinese Hindu culture. This cultural triumph has succeeded in positioning art as an important element in the context of the implementation of regional culture with Hinduism in Bali specifically. Gamelan Batel is an alit that is classified as middle gamelan used to accompany wayang kulit, barong bangkal and barong landung. In many ways this barrier is a procession accompaniment, because it can be played while walking. The existence of Gamelan Batel is told to begin to be studied by artists in the village of Sibanggede for the needs that are felt to be very important in people's lives. Besides that Gamelan Batel in Sibanggede has a function that is very closely related to Hindu religious ceremonies. In the ritual of the god yad, for example, in each house or pretending to be coercion (paibon), in the procession of Hindu religious ceremonies the Sibanggede community always involves the gamelan of this batel. There are several problems that arise first, changes in the function of batel gamelan which no longer become popular for puppeteers to preserve the traditional wayang puppet.